2014
DOI: 10.1254/jphs.14081fp
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Norepinephrine Transporter (NET) Inhibition on μ-Opioid Receptor (MOR)-Induced Anti-nociception in a Bone Cancer Pain Model

Abstract: Abstract. Although norepinephrine transporter (NET) inhibition has an additional effect on mopioid receptor (MOR)-mediated anti-nociception in inflammatory and neuropathic pain, its effect on cancer pain is not well characterized. We investigated the additional effect of NET inhibition on MOR activation using a mouse femur bone cancer (FBC) pain model by comparing the antinociceptive effect of the dual-acting opioids tramadol and tapentadol and the clinically used MOR-targeted opioids oxycodone and morphine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The present study demonstrated that tapentadol produces antinociception in both phases of the orofacial formalin test. This study agrees with previous reports showing that tapentadol produces antinociception when administered systemically in animal models Christoph et al, 2011;Bujalska-Zadro_ zny et al, 2015;Ono et al, 2014] including the orofacial formalin test [Lee et al, 2015]. Furthermore, in the present study a dose-related antinociceptive effect of ketorolac was observed in both phases of the orofacial formalin in agreement with previous observations [Miranda et al, 1993;L opez-Muñoz et al, 2004;Isiordia et al, 2010].…”
Section: Discussionsupporting
confidence: 94%
“…The present study demonstrated that tapentadol produces antinociception in both phases of the orofacial formalin test. This study agrees with previous reports showing that tapentadol produces antinociception when administered systemically in animal models Christoph et al, 2011;Bujalska-Zadro_ zny et al, 2015;Ono et al, 2014] including the orofacial formalin test [Lee et al, 2015]. Furthermore, in the present study a dose-related antinociceptive effect of ketorolac was observed in both phases of the orofacial formalin in agreement with previous observations [Miranda et al, 1993;L opez-Muñoz et al, 2004;Isiordia et al, 2010].…”
Section: Discussionsupporting
confidence: 94%
“…The present study shows that the systemic administration of tapentadol produces a dose‐dependent antinociceptive effect in a mouse model of visceral pain in agreement with other reports (Bujalska‐Zadrożny, Wolińska, Gąsińska, & Nagraba, ; Christoph, De Vry, Schiene, Tallarida, & Tzschentke, ; Ono et al, ; Schiene, De Vry, & Tzschentke, ) that included the acetic acid‐induced writhing test (Zapata‐Morales et al, ). Likewise, systemic diclofenac showed a dose‐dependent antinociceptive action in the acetic acid‐induced visceral pain assay in mice again in agreement with other reports (León‐Reyes, Castañeda‐Hernández, & Ortiz, ; Ortiz, ; Ortiz et al, ), that included the writhing test (Goh et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In vivo studies have dissected TP-induced opioid and noradrenergic actions 28. Nevertheless, the precise mechanism underlying the effect of TP on NeP should be better explained 29…”
Section: Discussionmentioning
confidence: 99%